2021
DOI: 10.30802/aalas-jaalas-21-000028
|View full text |Cite
|
Sign up to set email alerts
|

Serum Buprenorphine Concentrations and Behavioral Activity in Mice After a Single Subcutaneous Injection of Simbadol, Buprenorphine SR-LAB, or Standard Buprenorphine

Abstract: Buprenorphine, an analgesic commonly used in rodent surgery, requires repeated dosing every 4 to 6 h in order to provide adequate analgesia. However, redosing requires repeated handling, which may itself cause stress. Buprenorphine SR-LAB, which reportedly maintains serum levels of buprenorphine greater than 1 ng/mL for 48 to 72 h, is commercially available. However, the viscosity of the product and small dosing volumes make accurate dosing a challenge. Simbadol is a concentrated formulation of buprenorphine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As sustained release Bup works to reduce pain for days [ 19 , 74 ] and alterations in opioid signaling in astrocytes alters mechanical sensitivity [ 66 ], the WNT was performed to investigate potential Bup-SR-Lab-associated changes in somatosensory sensitivity 4w following cFPI or sham injury. In agreement with previous studies from both our and other groups [ 24 , 28 , 30 , 31 ], animals sustaining cFPI displayed hypersensitivity and agitation to the stimulation as compared with animals sustaining sham injury at 4w post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…As sustained release Bup works to reduce pain for days [ 19 , 74 ] and alterations in opioid signaling in astrocytes alters mechanical sensitivity [ 66 ], the WNT was performed to investigate potential Bup-SR-Lab-associated changes in somatosensory sensitivity 4w following cFPI or sham injury. In agreement with previous studies from both our and other groups [ 24 , 28 , 30 , 31 ], animals sustaining cFPI displayed hypersensitivity and agitation to the stimulation as compared with animals sustaining sham injury at 4w post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…XRB (Ethiqa) is currently the only pharmaceutical grade FDA-indexed extended-release buprenorphine formulation that is approved for use in mice and rats. 29,57 In multiple strains of mice and rats, pharmacokinetic studies revealed a single injection of XRB (Ethiqa) provides therapeutic plasma concentrations for 48-72 h. 1,4,21,22,23,26,31,32,40 Additionally, XRB (Ethiqa) has a superior safety profile and long-lasting analgesia effects of up-to 72 h in mice and rats after a single subcutaneous injection. 3,7,16,19,24,40,48 Our results indicate in swine XRB (Ethiqa) provides longer therapeutic buprenorphine concentrations, consistent with what is observed in other non-rodent species and swine breeds.…”
Section: Discussionmentioning
confidence: 99%
“…As sustained release Bup works to reduce analgesia for days 19,75 and alterations in opioid signaling in astrocytes alters mechanical sensitivity 67 , the WNT was performed to investigate potential Bup-SR-Labassociated changes in somatosensory sensitivity 4w following cFPI or sham injury. In agreement with previous studies from both our and other groups 24,28,30,31 , animals sustaining cFPI displayed hypersensitivity and agitation to the stimulation as compared with animals sustaining sham injury at 4w post-injury.…”
Section: Discussionmentioning
confidence: 99%